Alpha-1 Antitrypsin Augmentation Therapy Improves Survival in Severely Deficient Patients with Predicted FEV1 Between 10% and 60%: A Retrospective Analysis of the NHLBI Alpha-1 Antitrypsin Deficiency Registry - Rahaghi FF; Monk R; Ramakrishnan V; Beiko T; Strange C (International Journal of COPD, 2020)
Franck F Rahaghi,1 Richard Monk,2 Viswanathan Ramakrishnan,3 Tatsiana Beiko,2 Charlie Strange2 1Department of Pulmonary and Critical Care, Cleveland Clinic Florida, Weston, FL, USA; 2Division of Pulmonary, Critical Care, Allergy and Sleep Medicine, Medical University of South Carolina, Charleston, SC, USA; 3Department of Public Health Sciences, Medical University of South Carolina, Charleston, SC, USACorrespondence: Franck F RahaghiDepartment of Pulmonary and Critical Care, Cleveland Clinic Florida, Weston, FL, USATel +1 954 659 5450Fax +1 954 6595451Email rahaghf@ccf.orgPurpose: The extent of the survival benefit of augmentation therapy for alpha-1 antitrypsin deficiency (AATD) in individuals with advanced COPD is difficult to define. We performed a retrospective analysis using all available data from the observational registry of individuals with severe deficiency of alpha-1 antitrypsin (AAT) conducted by the NHLBI investigators.Patients and Methods: Individuals (N=1129) with severe deficiency of AAT were evaluated for mortality using all data sources and stratified by 10% increments of baseline forced expiratory volume in 1 second (FEV1) percent predicted and by augmentation therapy status (ever receiving versus never receiving). Kaplan–Meier survival curves were constructed for each of the deciles comparing survival in treated vs non-treated groups. A multivariable model was performed to define the correlates of survival in individuals with FEV1 < 30% predicted.Results: Amongst all subjects, augmentation was associated with improved survival (p< 0.0001). Among the individuals ever receiving augmentation therapy, survival was better than for those not receiving augmentation at all 10% increments of FEV1% predicted from 10% to 60% (P values < 0.05 in all deciles). In subgroups of participants with hyperinflation defined as residual volume (RV)> 120% predicted and in subgroups of participants with reduced diffusing capacity for carbon monoxide (DLCO) < 70% predicted, there was significantly better survival for those ever receiving augmentation therapy than for those who never received augmentation (p< 0.001). A multivariable analysis showed that mortality benefit is influenced by age, DLCO % predicted, and augmentation therapy.Conclusion: There is a survival benefit from augmentation therapy in AATD between FEV1 values in the 10– 60% predicted range. Screening and treatment of AATD patients should therefore not be limited by the severity of illness as defined by FEV1.Keywords: alpha-1 antitrypsin deficiency, COPD, mortality, augmentation therapy, FEV1, survival